2007
DOI: 10.1267/ahc.07011
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Protein Kinase N (PKN) in the Hydrocephalic Rat Brain

Abstract: AHC PKN (protein kinase N; also called protein kinase C-related kinase (PRK-1)), is a serine/threonine protein kinase that is ubiquitously expressed in several organs, including the brain. PKN has a molecular mass of 120 kDa and has two domains, a regulatory and a catalytic domain, in its amino-terminals and carboxyl-terminus, respectively. Although the role of PKN has not been fully elucidated, previous studies have revealed that PKN is cleaved to a constitutively active catalytic fragment of 55 kDa in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…One possible explanation would be that other PKN isoforms could compensate for the loss of PKN3 function in the context of tumor. PKN1, in particular, might be stimulated in the stromal cells inside of a tumor, because ischemic/hypoxic stress, which frequently happens inside of a tumor, is reported to activate or enhance the expression of PKN1 57 58 59 60 .…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation would be that other PKN isoforms could compensate for the loss of PKN3 function in the context of tumor. PKN1, in particular, might be stimulated in the stromal cells inside of a tumor, because ischemic/hypoxic stress, which frequently happens inside of a tumor, is reported to activate or enhance the expression of PKN1 57 58 59 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PKN1 is also achieved by caspase-3–mediated cleavage, resulting in a constitutively active protein product missing the regulatory N-terminus ( 9 ). This form of deregulated PKN1 activation occurs during apoptosis ( 10 ) and has been linked to various insults to the brain ( 11 14 ). We have previously reported that PKN1 is part of a purine-nucleoside signaling cascade involved in the protection of hypoxic neuronal cultures and cell lines in vitro ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following the surgery, all animals were monitored daily to evaluate body weight, head circumference, gait, and general appearance for any signs of hydrocephalus development. Like human patients, rats with kaolin-induced hydrocephalus present gait disturbances [2,26,27]. A set of reflexes and motor tests were conducted to evaluate the motor function of the animals.…”
Section: Surgical Induction Of Hydrocephalusmentioning
confidence: 99%